Establishment of a new genus for Cyclograpsus lophopus Nobili, 1905, within Sesarmidae Dana, 1851 (Crustacea: Decapoda: Brachyura) - Naruse, Tohru; Ng, Ngan Kee (Zootaxa, 2012)
The examination of the type series of the poorly known Cyclograpsus lophopus Nobili, 1905, which was originally placedin the varunid genus, Cyclograpsus H. Milne Edwards, 1837, has revealed that it belongs instead to the family SesarmidaeDana, 1851. A new genus is also described for C. lophopus because of its very distinct morphological characters, e.g. entire and nearly circular contour of the carapace with trigonal ocular peduncles, and short and flattened ambulatory legs.